CCR5 Δ32 homozygous cord blood allogeneic transplantation in a patient with HIV: a case report. Issue 6 (June 2015) - Duarte, Rafael F; Salgado, María; Sánchez-Ortega, Isabel; Arnan, Montserrat; Canals, Carmen; Domingo-Domenech, Eva; Fernández-de-Sevilla, Alberto; González-Barca, Eva; Morón-López, Sara; Nogues, Nuria; Patiño, Beatriz; Puertas, Maria Carmen; et al.
Summary: Background: Allogeneic donor CCR5 Δ32 homozygous haemopoietic cell transplantation (HCT) provides the only evidence to date of long-term control of HIV infection. However, availability of conventional CCR5 Δ32 homozygous donors is insufficient to develop this as a therapeutic strategy further. Methods: We present a 37-year-old patient with HIV-1 infection and aggressive lymphoma who had disease progression after five lines of radiochemotherapy including an autologous HCT, and in the absence of matched sibling donors, received an allogeneic HCT with four of six HLA-matched CCR5 Δ32 homozygous cord blood cells (StemCyte, Covina, CA), supported with purified CD34+ cells from a haploidentical sibling. Blood or tissue samples were obtained before and weekly after HCT to monitor transplant and HIV infection, including chimerism analysis, CCR5 genotyping and viral tropism, viral isolation and sequence, viral reservoir analysis, immune activation and proliferation, and ex-vivo cell infectivity assays. Combined antiretroviral therapy continued during the procedure. Findings: The patient's HIV was CCR5-tropic by genotypic and phenotypic analyses. Baseline latent reservoir tests showed HIV DNA copies in bulk and resting CD4 T cells and in gut-associated lymphoid tissue, CD4 T-cell-associated HIV RNA, replication competent viral size of 2·1 copies per 10 7 CD4 T cells, and single copy assay of 303 copies per mL. After HCT, plasma HIV DNA load was undetectable by ultrasensitive analyses. Upon cord blood full chimerism, the patient's CCR5 Δ32 homozygous CD4 T cells responded to proliferation and activation stimuli and became resistant to infection by the patient's viral isolate and by laboratory-adapted HIV-1 strains. Death related to lymphoma progression regretfully prevented long-term monitoring of the patient's viral reservoir. Interpretation: CCR5 Δ32 homozygous cord blood reconstitution can successfully eliminate HIV-1 and render the allogeneic graft recipient's T lymphocytes resistant to HIV infection. Thus, they build on the evidence available to strongly support the use of cord blood as a strategic platform for a broader application of non-functional CCR5 transplantation to other infected individuals. Funding: Spanish Secretariat of Research, the American Foundation for AIDS Research (amfAR).